1964
DOI: 10.2307/1933844
|View full text |Cite
|
Sign up to set email alerts
|

The Spruce-Fir Forests of the Catskill Mountains

Abstract: Twenty—two forest stands of the Catskill Mountains, New York, in which spruce (Picea rubens), balsam (Abies balsamea), or both were present in the tree canopy, were sampled by means of the quarter method. A matrix of index of similarity values was calculated on the basis of the relative frequency, density, and dominance (importance value) of the mature trees plus the relative density of the saplings. From the matrix a two—dimensional ordination was constructed. The stands were distributed on the first order pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…Tsuga and Fagus trees are characteristically found in more mesic sites and in older forests in the Lake George region (NICHOLSON et ai, 1979) while P. strobus and Quercus are early successional species in the Catskills (McINTOSH, 1972). Values of Acer pollen are quite high, and indicate the importance of Acer trees in the forest around Clear Pond ; Acer pollen values (which amount to 3-7 %) were greater than those of the "érablière" of southern Québec (RICHARD, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Tsuga and Fagus trees are characteristically found in more mesic sites and in older forests in the Lake George region (NICHOLSON et ai, 1979) while P. strobus and Quercus are early successional species in the Catskills (McINTOSH, 1972). Values of Acer pollen are quite high, and indicate the importance of Acer trees in the forest around Clear Pond ; Acer pollen values (which amount to 3-7 %) were greater than those of the "érablière" of southern Québec (RICHARD, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The vegetation of the zone roughly between 500 and 1100 m elevation is typical of northern hardwood forests throughout the northeastern United States. McIntosh (1972) reported sugar maple to be the most common tree in the Catskills, being present in 81% of the stands sampled and the leading dominant in 27% of them. Beech was second, being present in 70% of the stands and the leading dominant in 16%, and yellow birch (Betula alleghaniensis Britt.)…”
Section: Site Descriptionmentioning
confidence: 99%
“…McIntosh (1972) found that beech composed 12.8% of the total tree density in the Catskills based on data collected from 1960 to 1963. We found beech to compose 17% of the total density.…”
Section: Beech Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…ow ever, while the forest mosaic indicator will help to define the range of acceptable forest compositions to be maintained in a managed landscape, it is through an understanding of regeneration dynamics, such as the distinction between the effect of natural disturbances versus harvesting practices, that the long-term impact of forest management activities on the forest mosaic will be made. In fact, it is recognised that harvest activities may transform the composition and structure of some forests mostly by altering regeneration processes (and forest age structures) and by promoting tree species that are better adapted to new conditions generated by cutting disturbance (Sicama 1971, McIntosh 1972, Whitney 1986, Carleton and MacLellan 1994.…”
Section: Landscape Level Planning Indicatormentioning
confidence: 99%